PENGELOLAAN RETRIBUSI PELAYANAN PASAR DI KABUPATEN PEMALANG - Noviani, Anita; Masdjojo, Gregorius N (Jurnal Ilmiah Telaah Manajemen, 2018)
The objective of this research is to analyze the Expected Oportunity Loss (EOL) in management of market retribution services in Pemalang distric. The sample of this research is three markets from the north and five markets from the south. The reason is because market from the south still used the market days and it didn't happen market from north because there are many thousands of traders. Data collection methods using direct interview to traders, retribution collectors,and market managers. After doing the research, the writer knows the causes Expected Oportunity Loss (EOL) is undisciplined retribution collectors who not understood of regulations so that they only receive retribution without calculating the tariff. We know that market management consists of planning, resource empowerment, finance and supervision but based on the results of the study it can be seen that the planning of the target market service retribution is only based on the calculation of the percentage of the previous year's target and it do not based on existing potential. The writer also knows the resource empowerment not optimal yet because officers still assume that they are collectors not being a managers then markets difficult to develop and innovate and also insufficient infrastructure. In terms of finance also is not optimal because market managers do collecting tax not appropriate with regional regulations. And also based on the research, the writers knows that monitoring and inpection about finance does not do reguraly at market and it can cause aberration. Key words: Planning, Empowering Human Resources, Finance, Supervision.